Analisis Efektivitas Desain User Interface Aplikasi JKN Mobile Berdasarkan Teori Usability Heuristic of UI Principles - M. Alif Wicaksono; M Garry Saputra; Abiel Yizrel Panggula (Pixel :Jurnal Ilmiah Komputer Grafis, 2025)
This study evaluated the effectiveness of the JKN Mobile interface using Nielsen’s Usability Heuristic Principles to identify issues that affect clarity, consistency, and user navigation. The research applied a descriptive qualitative approach through interface observation and visual analysis, focusing on typography, layout, color usage, iconography, and feedback mechanisms. The findings showed that several essential elements of system status were not clearly presented, such as loading indicators, data update information, and synchronization cues. Inconsistencies in icon style, visual hierarchy, and button functions further reduced predictability and increased the cognitive load on users. Some screens also displayed incomplete content and unclear action mapping, which disrupted task flow. The study concludes that improving visual hierarchy, standardizing interface components, refining navigation paths, and providing clearer feedback can strengthen usability and support the application’s role as an accessible digital public service.